Does soaking time during disinfestation affect germination rates in Dendrobium? (Bioscience Journal, 2020)
Asymbiotic germination is considered an efficient and viable technique that can increase germination rates. The effect of type and concentration of disinfestants, and the exposure time to disinfestants may differ according to the plant species. Therefore, species-specific standardization of disinfestation agent and procedure is necessary to achieve optimal germination rates. The objective of this study was to determine a disinfestation methodology to increase in vitro germination rates and the early development of seedlings of Dendrobium nobile and Dendrobium phalaenopsis, using different times for seed disinfestation and different culture media. Seeds were disinfected by soaking in a 0.8% sodium hypochlorite solution for 5 or 15 min under aseptic conditions, after which seed suspensions were either washed with water or left unwashed. Next, they were seeded in culture flasks containing four different culture media (MS, ½MS, K, and VW). The flasks were then transferred to a growth room under controlled photoperiod and temperature, where they remained under an irradiance of 20 μmol m-2 s-1. Germination rates of the species were evaluated 45 days after placement in the culture flasks. A higher germination rate was observed when the seeds were triple washed, regardless of the culture medium or soaking time. Seed soaking disinfestation for 5 min is also recommended. MS and ½MS media were the most effective culture media in promoting in vitro germination of the species under study.